2022
DOI: 10.1111/vop.13051
|View full text |Cite
|
Sign up to set email alerts
|

Ocular surface physiology and aqueous tear secretion in cats of diverse cephalic conformations

Abstract: Objective: To describe normative ocular surface and aqueous tear testing data for cats of various cephalic conformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
3
1
Order By: Relevance
“…The long-standing belief that sympathetic stimulation induced by stress can temporarily reduce tear production in feline species 11 , 12 has been contradicted by recent evidence. 7 , 13 18 Likewise, the findings of the present study do not support this theory because the STT-1 values were significantly higher during the stress-inducing intervention than during the day without stress stimuli. Notably, 23/24 evaluated animals showed an increase in tear production during the stress-inducing intervention.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…The long-standing belief that sympathetic stimulation induced by stress can temporarily reduce tear production in feline species 11 , 12 has been contradicted by recent evidence. 7 , 13 18 Likewise, the findings of the present study do not support this theory because the STT-1 values were significantly higher during the stress-inducing intervention than during the day without stress stimuli. Notably, 23/24 evaluated animals showed an increase in tear production during the stress-inducing intervention.…”
Section: Discussioncontrasting
confidence: 96%
“…7,13,18 Despite sex differences being reported in a retrospective study of dry eye (keratoconjunctivitis sicca) in dogs, 21 most research findings indicate that tear production is equivalent in both sexes of healthy dogs 22,23 and cats. 7,13,16 The neuter status has been reported to influence the STT-1, showing higher values in neutered cats. 13,16 In the context of our study, no significant difference in STT-1 values was observed between male and female cats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations